An unusual case of a large fibroepithelial stromal polyp presenting as a nipple mass - Shaaban, Abeer M (BioMed Central, 2013)
BACKGROUND: Fibroepithelial stromal polyps (FESP) are benign lesions that typically occur in the genital area and are known to represent a diagnostic challenge for pathologists. Not only do they have a spectrum of morphological changes that ranges from bland morphology to rather atypical appearances, but they also share morphological features with a number of benign and malignant lesions. This is a report of a rare presentation of a FESP of the breast. CASE PRESENTATION: We describe an unusual case of a large polypoid mass arising from the nipple and connected to it by a long pedicle in a female of 45. The lesion comprised spindle and stellate shaped cells with bizarre stromal giant cells. The morphological and immunohistochemical diagnostic features are provided together with a discussion of possible mimics. CONCLUSION: FESPs may occur in the female breast. It is important to differentiate the lesion from other benign and malignant spindle cell lesions particularly metaplastic carcinoma.